ETIKA KOMUNIKASI PUBLIK DAN DAMPAKNYA TERHADAP STABILITAS MASYARAKAT (STUDI KASUS: STATEMENT AHMAD SAHRONI): Implikasi Etika dan Stabilitas Sosial dalam Komunikasi Politik Digital - Umar Sahid; Dewi Asih Nusantari; Syifa Hasna Afifah; Khalisya Tzanisa; Muhammad Isa Asyrofuddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Public communication ethics play a crucial role in maintaining societal stability, particularly when messages are delivered by influential political figures. This study examines Ahmad Sahroni's statement in the context of the August 25, 2025, demonstrations, which elicited widespread public reaction. The research focuses on how Sahroni's communication ethics impacted social stability, and how the media and the public responded to the statement. The method used was a descriptive qualitative approach with literature analysis. The theoretical framework included Aristotle's rhetorical theory (ethos, logos, pathos), McCombs & Shaw's agenda-setting theory, Shannon & Weaver's communication model, political communication theory, and communication ethics theory. The results show that Ahmad Sahroni's statement did not align with the principles of communication ethics, as it created a perception of demeaning the public and fueled social dissatisfaction. The mass media then amplified this issue through agenda-setting, thus amplifying its impact on public opinion. The resulting disruption to societal stability resulted in protests, decreased trust in the House of Representatives (DPR), and increased political tension. This study emphasizes the importance of public communication ethics in building trust and maintaining social stability. For students, this study provides practical learning about the close relationship between political communication, ethics, and their impact on social life.